Total dose and frequency of administration critically affect success of nasal mucosal tolerance induction. Issue 6 (1st June 2001) - Jiang, Hui-Rong; Taylor, Neil; Duncan, Linda; Dick, Andrew D; Forrester, John V
Abstract : AIMS: Nasal tolerance induction with autoantigens can effectively protect against a variety of experimental models of autoimmune disease. The aims of this study were to characterise the dosage and kinetics of inhibition of experimental autoimmune uveoretinitis (EAU) via intranasal administration of the uveitogenic antigen interphotoreceptor retinal binding protein (IRBP) in the murine model of IRBP induced EAU. METHODS: B10RIII mice were tolerised by intranasal administration of IRBP either with a long term multiple low dose or a short term/high dosing regimen before subcutaneous immunisation with IRBP in complete Freund's adjuvant (CFA). On day 15 post-immunisation, mice were killed and eyes were removed for histological examination and quantification of inflammatory cell infiltration and degree of target organ (rod outer segment, ROS) destruction. RESULTS: Nasal administration of multiple low doses of IRBP (1 μg or 3 μg IRBP per mouse per day for 10 days) significantly protected mice from IRBP induced EAU. Short term/high dose regimens were only effective when given either as a single or, at most, as two consecutive doses (40 μg per dose). Multiple doses in the range of 45–120 μg over 3 days afforded no protection. CONCLUSIONS: These results indicate that both dose and frequency of intranasal antigen administration are pivotal to tolerance induction and subsequent suppression of T cell mediated autoimmune disease.